KAJIAN PENENTUAN KECEPATAN MAKSIMAL YANG BERKESELAMATAN PADA BLACKSPOT DI RUAS JALAN KRIAN – BALONGBENDO SIDOARJO - Supriyatno, Dadang (FSTPT Indonesia, 2015)
Krian roads connecting cross-Balongbendo a Surabaya-Yogyakarta anatara traversed by various types of vehicles with an average speed that is high enough to potentially cause major traffic accidents. Therefore, determination of technical studies conducted at a maximum speed of these roads. Based on the traffic accident data and daily average in the area of accident analysis and calculation of the actual speed of the Safer. From the analysis of the obtained results and Blacksideblackspot determination and the actual speed of the results obtained in these roads Safer.